Transnational companies and production global networks - Golea, Valentina; Niculescu, Nicoleta; Niculescu, Dragos (Studies and Scientific Researches. Economics Edition, 2010)
Internationalizing a company is an objective process. The historical reality shows that, while developing, the company tends to exceed its local, national and regional limits of business environment, in order to expand its activity into the global economic space, whose formatting is possible through the very company’s movement towards exterior. This process is based on the imminent expansionism of the market forces, their tendencies to invade the environment “unmarketedly”, and to include it in an economic system based on the market mechanism. Companies involve themselves in the international production because they have a specific competitive advantage which is best exploited in this way. The advantage can consist in a product or in a brevetted technique, but it may also include management techniques or such as: company’s or its employee’s qualification and expertise.